Carbon sink strength of a Mediterranean cork oak understorey: how do semi-deciduous and evergreen shrubs face summer drought? - Correia, A. C.; Costa e Silva, F.; Correia, A. V.; Hussain, M. Z.; Rodrigues, A. D.; David, J. S.; Pereira, J. S. (Journal of Vegetation Science, 2013)
Questions How do semi-deciduous and evergreen shrubs exploit environmental resources during summer drought? What is the contribution of the understorey shrubby layer to ecosystem carbon assimilation? To what extent are carbon balance and transpiration impacted by a rain pulse? Location Cork oak open woodland in the Mediterranean region. Methods We used closed dynamic light and dark chambers to measure gas exchange (CO2 and H2O) in the dominant shrub understorey species Cistus salviifolius, Cistus crispus (semi-deciduous) and Ulex airensis (evergreen), together with plant physiological and morphological measurements during summer drought and autumn recovery. A hyperbolic light response model constrained by vapour pressure deficits was fitted for up-scaling shrub photosynthesis to the ecosystem level. The data were compared, on a daily and daytime basis, with gross primary productivity estimates from ecosystem eddy-covariance flux measurements. Results The onset of summer drought led to a significant leaf area reduction in semi-deciduous species. A general decrease in photosynthesis in all species was observed, while evapotranspiration and above-ground respiration fluxes contrasted among species during summer progression and autumn recovery. The shallow-rooted C. salviifolius was able to use light more efficiently than the other two species, although with poor stomatal control over water loss and consistently higher above-ground respiration rates, leading to lower water and carbon use efficiencies when compared with C. crispus. The deep-rooted shrub U. airensis maintained higher leaf water potentials and very low photosynthetic rates while decreasing transpiration rates throughout the summer drought. A summer rain pulse showed that shallow-rooted shrubs use water in an opportunistic way, with immediate leaf rehydration and concomitant photosynthesis increments. Conversely, deep-rooted shrubs (U. airensis) were unresponsive, only recovering photosynthesis with high soil water content. An opportunistic growth response may be disadvantageous to shallow-rooted shrubs in a future climate with extended dry summers and higher probability of rain pulse events. The prominent increase in transpiration rates and plant respiration costs observed during the dry conditions that followed the rain pulse, led to a reduced plant ability to recover after autumn rains. Conclusions The shrubs that naturaly colonized this montado understorey showed contrasting strategies to overcome summer drought, suggesting an efficient mosaic exploitation of seasonal environmental resources. The contribution of these shrubs to total ecosystem CO2 uptake during summer and autumn recovery was 17%. This high contribution implies that shrub density management decisions should consider a carbon balance perspective.
Keywords: Cistus sp; CO2; Eddy-covariance; H2O; Mediterranean; partitioning; Shrubs; Ulex sp; up-scaling